Physical Activity Monitoring Model to Measure the Appropriateness of Weekly Physical Activity for the World Health Organization’s Physical Well-Being and Health Claims - Ceruso, Rosario; Giardullo, Giuseppe; Di Lascio, Giuseppe; Cusano, Pompilio; Sannicandro, Italo (Teorìâ ta metodika fìzičnogo vihovannâ, 2024)
Objectives. The study aimed to test an agile monitoring tool to correlate physical activity levels for the 2 target age groups of school education with energy consumption. Materials and methods. The sample consisted of 42 students, divided into two age-based groups: between 5 and 8 years of 24 and between 13 and 16 years of 18. Both were administered the adapted International Physical Activity Questionnaire (IPAQ), comprising ten questions, the first of which distinguished active athletes from others participants. The remaining nine questions were divided into sections: “intense activities,” “moderate activities,” and “walking only.” The data on the amount of physical activity undertaken in the past seven days were converted to energy expenditure through the evaluative unit of Metabolic Equivalent of Task (MET). Results. For subjects between 5-8 years who were active in sports, the weekly average was 3355.2 METs, with 1577 for intense activities, 1617 for moderate activities, and 159.7 for walking. Among subjects in the 13-16 years age group who were active in sports, the weekly average was 3799.5 METs, with 3376 for intense activities, 577.6 for moderate activities, and 529.9 for walking. For the same age group who were not engaged in sports activity, the weekly average was594.5 METs, with 20 for intense activities, 360 for moderate activities, and 214.5 for walking. Conclusions. The findings show that it is possible to use the physical activity monitoring tool proposed in the study, with the measurement of METs.